Pemahaman Umat tentang Makna Persembahan dan Korelasinya dengan Ketidakhadiran pada Misa Hari Minggu (Studi Kasus di Stasi St. Maria Imakulata Oeltua, Paroki St. Yosef Pekerja Penfui) - Eugenius Koresy Bour; Yoseph Freinademetz Runesi (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2025)
This study aims to explore and explain the understanding of Catholics at Stasi St. Maria Imakulata Oeltua, Parish of St. Josef Pekerja Penfui, regarding the meaning of the offering and its correlation with their absence from Sunday Mass. This study is a qualitative study that uses a literature approach. The results of this study show that a number of Catholics at Stasi St. Maria Imakulata Oeltua have a wrong understanding about the meaning of the offering. According to them, offering is not only as a form of gratitude to God, but also a condition to get God’s blessing. That point of view has to do with their absence in the Eucharist on Sunday. They will not attend the Eucharist on Sunday when they do not have money to give to the Church as a form of their offering. The Eucharist is actually the source and peak of the faith of Christians. The main and first offering in the Eucharistic Celebration is the self and the heart of the Christians themselves. In other words, the main and most important offering of Christians is the offering of self or the offering of whole life; and not money. Money is needed to sustain the life and ministry of the Church, but it is not the main thing of the Christians offering. Therefore, to correct this misunderstanding, catechesis needs to be held as a means of teaching the true Catholic faith.